Hippocampal non-theta state: The “Janus face” of information processing - Mysin, Ivan; Shubina, Liubov (Frontiers in Neural Circuits, 2023)
The vast majority of studies on hippocampal rhythms have been conducted on animals or humans in situations where their attention was focused on external stimuli or solving cognitive tasks. These studies formed the basis for the idea that rhythmical activity coordinates the work of neurons during information processing. However, at rest, when attention is not directed to external stimuli, brain rhythms do not disappear, although the parameters of oscillatory activity change. What is the functional load of rhythmical activity at rest? Hippocampal oscillatory activity during rest is called the non-theta state, as opposed to the theta state, a characteristic activity during active behavior. We dedicate our review to discussing the present state of the art in the research of the non-theta state. The key provisions of the review are as follows: 1) the non-theta state has its own characteristics of oscillatory and neuronal activity; 2) serotonergic projections of raphe nuclei cause and maintain the non-theta state through the suppression of theta rhythmic activity in the medial septum; 3) there is no consensus in the literature about cognitive functions of the non-theta-non-ripple state; 4) the antagonistic relationship between theta and delta rhythms observed in rodents is not always observed in humans. Most attention is paid to the non-theta-non-ripple state, since this aspect of hippocampal activity has not been investigated properly and discussed in reviews.